Satisfaction of patients and primary care professionals with a teleophthalmology-based screening programme for diabetic retinopathy in a rural area in Castilla y León, Spain - Yolanda Valpuesta Martin; Gabriela Estefanía Pacheco Callirgos; Teresa Marcela Maroto Martín; Monserrat Piriz Veloso; Susana Hernández Santamaría; María Isabel López Gálvez (James Cook University, 2020)
Introduction: Diabetic retinopathy (DR) is the leading cause of blindness in working-age adults in most developed countries. Early diagnosis and early treatment for retinopathy can reduce the incidence of severe loss of vision in a high percentage of sight-threatening DR. However, sight-threatening DR is asymptomatic in a high percentage of patients and no more than 50% of the diabetic patients are reviewed periodically in ophthalmology, mainly in rural areas. Telemedicine facilitates the exchange of information among professionals, reducing unnecessary journeys for patients who live in rural or remote areas. The survey of satisfaction is a highly useful quantitative instrument to obtain information directly from the users of a screening program. One aim of this study has been to determine the prevalence of DR in a sample of diabetic patients from a rural area of Spain and to classify DR patients according to the type and severity of this complication of the disease. The other main target was to evaluate the degree of satisfaction in both diabetic patients and professionals with a teleophthalmology-based screening program of DR. Methods: A sample of 114 diabetic patients included in a new teleophthalmology program for the screening of DR in Castilla y León, Spain, were asked to take part in an in-person survey designed to evaluate the degree of satisfaction. This sample was obtained through a consecutive non-probability sampling technique, out of a total of 752 diabetic patients who underwent a retinography screening program in a distant rural healthcare center. The survey assessed aspects related to the information about the program the patients received, the organization of the center, the way the test was conducted and the reception of the results. All the included participants consented to participate in this study. Additionally, an anonymous survey was conducted via email. The sample was made up of 10 professionals responsible for taking the retinal images from the patients included in the study. This survey assessed their degree of satisfaction with their training, the way the test was carried out, the support from their managers and how this activity influenced their relationship with their patients. Results: A high percentage of patients with DR in the study sample had a form of sight-threatening retinopathy (29.4%), which in this program is a criterion of referral to be assessed by an ophthalmologist. Of the surveyed patients, 93.8% scored eight points or higher for their degree of general satisfaction with the activity. All of them claimed they would prefer to continue their exploration at the healthcare center instead of going to the hospital. As regards the professionals, 70% scored eight points or more in terms of their degree of general satisfaction with the activity, whereas 20% scored between five and seven. One professional did not respond to the question. Finally, 90% stated that they would continue performing the activity, while the remaining 10% answered no. Conclusion: According to the high percentage of patients diagnosed with vision-threatening DR in this study, an early diagnosis of this complication of diabetes seems to be important. Teleophthalmology enhances patient accessibility to the healthcare system, making early diagnosis of DR easier, with a high degree of satisfaction among patients and healthcare professionals.